(untitled) (Journal of the College of Basic Education, 2025)
Arab society is facing challenges resulting from the rapid scientific development and the massive growth in information, which made us urgently need to build a thinking generation and teach the learner how to learn and how to think by acquiring knowledge and processing it by employing and developing his mental processes. To bring about this change requires a material and moral shift in the methods and strategies of education in general and teaching in particular, to achieve the goals of society and education on the one hand, the needs of students and the requirements of the times on the other hand, and in the light of the available capabilities. Because of the low level of students’ attainment and their ability to recall scientific information and the scarcity of their adoption of scientific methods of thinking, and as a result of the foregoing, the researcher decided to adopt a strategy of cognitive realization, which may contribute to helping students understand and comprehend the study material and employing study skills and how to adopt the scientific method in their thinking. The research problem was identified in the following question: "Will the strategy of cognitive perception affect the achievement and development of scientific thinking among the students of the Institute of Fine Arts in the subject of teaching methods?" The objectives of the research were to identify: 1- The effect of the cognitive perception strategy on the achievement of the students of the Institute of Fine Arts in the subject of teaching methods. 2- The impact of the cognitive awareness strategy on developing scientific thinking among students of the Institute of Fine Arts in the subject of teaching methods.In order to ensure the achievement of the research objectives, the following hypotheses were formulated: 1- There are no statistically significant differences at the level of significance (0.05) between the mean scores of the experimental group students and the mean scores of the control group in the cognitive achievement test of the post-teaching methods course. 2- There are no statistically significant differences at the level of significance (0.05) between the mean scores of the students of the experimental group and the mean scores of the students of the control group in the dimension of scientific thinking scale. The research limits were: - Students of the Institute of Fine Arts for Boys, Baghdad Governorate Education Directorate, Al-Karkh Al-Ola. The curriculum prescribed by the feudal committee for teaching methods at the Institute of Fine Arts (2022-2023). The experimental approach was chosen with equal groups and the post-test for achievement and development, and the pre- and post-test for scientific thinking. After processing the results statistically and using statistical methods such as the t-test, Pearson’s correlation coefficient, the discrimination equation for the objective periods, the difficulty equation for the objective items, the equation for the effectiveness of false alternatives, the Qodder equation, the Kay-square test for good fit, the Wackeronbach equation for stability, and the square effect size equation u2, the results showed the following: 1- The impact of the cognitive perception strategy on the achievement of the students of the Institute of Fine Arts in the subject of teaching methods. 2- The impact of cognitive perception strategy on developing scientific thinking among students of the Institute of Fine Arts in the subject of teaching methods